Birds and climate change : impacts and conservation responses - Pearce-Higgins, James W.; Green, Rhys (Cambridge : Cambridge University Press, 2014)
From the red grouse to the Ethiopian bush-crow, bird populations around the world can provide us with vital insights into the effects of climate change on species and ecosystems. They are among the best studied and monitored of organisms, yet many are already under threat of extinction as a result of habitat loss, overexploitation and pollution. Providing a single source of information for students, scientists, practitioners and policy-makers, this book begins with a critical review of the existing impacts of climate change on birds, including changes in the timing of migration and breeding and effects on bird populations around the world. The second part considers how conservationists can assess potential future impacts, quantifying how extinction risk is linked to the magnitude of global change and synthesising the evidence in support of likely conservation responses. The final chapters assess the threats posed by efforts to reduce the magnitude of climate change.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Birds -- Climatic factors; Birds -- Conservation